2023
DOI: 10.1021/acs.molpharmaceut.3c00312
|View full text |Cite
|
Sign up to set email alerts
|

Role of Poloxamer 188 in Preventing Ice-Surface-Induced Protein Destabilization during Freeze–Thawing

Abstract: The phase behavior of poloxamer 188 (P188) in aqueous solutions, characterized by differential scanning calorimetry (DSC) and synchrotron X-ray diffractometry, revealed solute crystallization during both freezing and thawing. Sucrose and trehalose inhibited P188 crystallization during freeze−thawing (FT). While trehalose inhibited P188 crystallization only during cooling, sucrose completely suppressed P188 crystallization during both cooling and heating. Lactate dehydrogenase (LDH) served as a model protein to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…For example, hexagonal ice is observed in Figure C, while the ice peaks in the other patterns could not be reliably attributed to a specific physical form of ice. The same problem was reported recently . Despite the lack of reproducibility in ice phase formation, once formed, the ice phase did not exhibit any further transformation upon cooling.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…For example, hexagonal ice is observed in Figure C, while the ice peaks in the other patterns could not be reliably attributed to a specific physical form of ice. The same problem was reported recently . Despite the lack of reproducibility in ice phase formation, once formed, the ice phase did not exhibit any further transformation upon cooling.…”
Section: Resultssupporting
confidence: 74%
“…The same problem was reported recently. 29 Despite the lack of reproducibility in ice phase formation, once formed, the ice phase did not exhibit any further transformation upon cooling. This enabled us to characterize the phase behavior of the solutes in frozen solutions.…”
Section: Phase Behavior Of Excipients In Frozen Solutionsmentioning
confidence: 99%
“…We had previously observed that upon cooling P188 aqueous solution (4.0% w/v), in addition to ice, the solute had also crystallized. 13 During heating, several thermal events were observed, including (i) glass transition of P188 freeze concentrate (∼−70 °C), (ii) crystallization of P188 and the accompanying unfrozen water (∼−55 °C), and (iii) P188−ice eutectic melting (∼−18 °C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11, 12 We had previously documented the ability of P188 to prevent ice- surface-induced protein destabilization. 13 However, P188 crystallization in frozen solutions undermined its stabilization effect. On the other hand, the high crystallization propensity of P188 may bring about an additional functionality as a bulking agent in freeze-dried formulations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 Therefore, there is a need to evaluate their potential in future studies as alternative excipients in frozen NAA agent formulations and stabilization. Most recently, using lactate dehydrogenase as a model protein, Li et al 40 demonstrated that P188 could be full of promise for frozen NAA agent formulation. In summary, the current evaluations show a promising future for developing powder-based formulations for NAA agents to treat bacterial infections.…”
Section: Stabilized Dry Formulation Of Naa Agentsmentioning
confidence: 99%